Preparation method of resistive random access memory based on biopolymer film
By using apple glue polymer film and SiO2 nanoparticles to regulate the surface microstructure, low-cost and high-performance resistive memory are prepared, which solves the problems of high cost of traditional resistive memory materials and complex preparation processes, and achieves environmental protection and biocompatible and excellent performance.
Patent Information
- Application Number
- CN202411467203.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional resistive memory materials are costly and complex in preparation processes, which limits its large-scale application and industrial development.
Using apple glue polymer film as the functional layer, a resistance-change memory based on biopolymer film is prepared by lifting method and magnetron sputtering method, and combined with SiO2 nanoparticles to regulate the surface microstructure to form a low-cost and high-performance flexible resistance-change Memory.
It realizes a low-cost, easy-to-preparation and excellent performance resistive-variable memory, solves the problems of high cost and complex preparation processes of traditional resistive-variable memory, and has environmental protection and biocompatible, improving the stability and application potential of the device.
Smart Images

Figure CN119300701A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bioelectronic materials and devices, and in particular relates to a method for preparing a resistive random access memory based on a biopolymer film. Background Art
[0002] Flexible electronic technology is gradually becoming a research hotspot in the field of electronic technology due to its advantages such as low cost, simple production, environmental protection and sustainable development. As a new type of electronic component, resistive memory has shown great potential in data storage, signal processing and neuromorphic computing. However, traditional resistive memory mostly uses complex and expensive materials and technologies, which limits its large-scale application and industrial development. Therefore, it is of great significance to develop low-cost, high-performance and easy-to-prepare flexible resistive memory.
[0003] Pectin biopolymer material is a water-soluble biopolymer film material extracted from fruits such as apples and oranges. It contains rich easily ionized functional groups and has the potential to be used as a bioresistive material. Pectin polymer film is a biodegradable material. Due to its environmental friendliness and good biocompatibility, it has gradually become a new choice for the functional layer material of resistive memory. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a resistive random access memory based on a biopolymer film, so as to solve the problems of high material cost and complex preparation process of the existing resistive random access memory.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a method for preparing a resistive random access memory based on a biopolymer film, which is specifically implemented according to the following steps: Step 1, preparing a bottom electrode; Step 2, preparing an apple gum polymer film on the bottom electrode by using a Czochralski method as a functional layer; Step 3: depositing a layer of Au as a top electrode on the functional layer by magnetron sputtering to obtain a resistive random access memory.
[0006] As a preferred technical solution of the present invention, in step 1, the bottom electrode is prepared as follows: a mica sheet is used as a substrate, and a layer of Pt or Au is deposited on the mica sheet by magnetron sputtering to obtain a bottom electrode.
[0007] As a preferred technical solution of the present invention, in step 1, the bottom electrode is prepared as follows: polyethylene terephthalate is used as a substrate, and ITO is coated thereon to obtain the bottom electrode.
[0008] As a preferred technical solution of the present invention, in step 2, the preparation of apple gum polymer film is specifically as follows: prepare an apple gum solution with a mass fraction of 0.5% or 1% or 2% or 3% by mass, and use the pulling method to prepare the apple gum polymer film on the bottom electrode.
[0009] As a preferred technical solution of the present invention, in step 2, the apple gum solution is doped with SiO2 nanoparticles or amino SiO2 nanoparticles.
[0010] The beneficial effects of the present invention are as follows: the method for preparing a resistive random access memory based on a biopolymer film of the present invention utilizes the superior biological properties of apple gum polymer film and combines self-assembled SiO2 nanoparticles to regulate the surface microstructure of the polymer film to achieve the effect of optimizing the performance of the resistive random access memory. The resistive random access memory not only has excellent resistive random access performance, but also has the characteristics of low cost, easy preparation and good flexibility, thus solving the problems of high material cost and complex preparation process of existing resistive random access memory. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is the ultraviolet-visible spectrum (UV-Vis) of apple gum biopolymer film.
[0012] Figure 2 This is an atomic force microscope (AFM) image of apple gum biopolymer film.
[0013] Figure 3 This is the resistive switching performance curve of the Pt / Pectin / Au biopolymer thin film device on mica substrate.
[0014] Figure 4 This is the microscopic force curve (Force Curve) test diagram of apple gum biopolymer film.
[0015] Figure 5 This is an atomic force microscopy (AFM) image of apple gum biopolymer film doped with SiO2 nanoparticles.
[0016] Figure 6 This is the resistive switching performance curve of the PET-based ITO / Pectin / Pt doped SiO2 nanoparticles apple gum biopolymer film device.
[0017] Figure 7 This is the microscopic force curve test diagram of apple gum biopolymer film doped with SiO2 nanoparticles.
[0018] Figure 8 This is an atomic force microscopy (AFM) image of apple gum biopolymer film doped with amino-containing SiO2 nanoparticles.
[0019] Fig. 9 This is the resistive switching performance curve of the apple gum biopolymer film device based on PET-based ITO / Pectin / Pt doped with amino-SiO2 nanoparticles.
[0020] Fig.10 This is the microscopic force curve (ForceCurve) test diagram of apple gum biopolymer film doped with amino SiO2 nanoparticles. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0022] The method for preparing a resistive random access memory based on a biopolymer film of the present invention is specifically implemented according to the following steps: Step 1, preparing a bottom electrode; The bottom electrode is prepared as follows: a mica sheet is used as a substrate, and a layer of Pt or Au is deposited on the mica sheet by magnetron sputtering to obtain a bottom electrode; or polyethylene terephthalate is used as a substrate, and ITO is coated thereon to obtain a bottom electrode; Step 2, preparing an apple gum polymer film on the bottom electrode by using a Czochralski method as a functional layer; The preparation of the apple gum polymer film is as follows: prepare an apple gum solution with a mass fraction of 0.5%, 1%, 2%, or 3%, and use a Czochralski method to prepare an apple gum polymer film on a bottom electrode; the apple gum solution can be doped with SiO2 nanoparticles or amino SiO2 nanoparticles; Step 3: depositing a layer of Au as a top electrode on the functional layer by magnetron sputtering to obtain a resistive random access memory.
[0023] The reason why the present invention selects high-purity food raw material apple gum as the functional layer material is that apple gum contains easily ionized functional groups such as carboxyl and hydroxyl, which are conducive to the occurrence of resistance transformation behavior. The present invention uses the pulling method to prepare the film, and the instruments involved are homemade by Xi'an University of Technology. Prepare 0.5wt%, 1wt%, 2wt% and 3wt% apple gum solutions respectively, and after completely dissolving in deionized water, let it stand for 2 hours before starting to pull the film. Use the clip on the device to clamp the polyethylene terephthalate (PET) substrate plated with the bottom electrode, pull down the pull-down film device switch, and pull it from the solution at a uniform speed of 20 mm / s, then let it stand in the air to dry, and repeat the operation 2-4 times to make the film quality better and reduce defect holes.
[0024] Apple gum or apple gum / SiO2 nanoparticle composite solution is uniformly coated on the bottom electrode by the pulling method to form a thin film. The morphology and performance of the biopolymer film are optimized by controlling parameters such as pulling speed, solution concentration and drying conditions.
[0025] Preparation of resistive random access memory: Based on the above-mentioned film, a resistive random access memory with a sandwich structure of apple gum polymer film is prepared, such as PET-based ITO / Pectin / Pt (Au) resistive random access memory. During the experiment, the experimental parameters of the top electrode and the bottom electrode based on the PET substrate and the mica substrate are exactly the same, but in order to improve the resistive random access properties of the apple gum functional layer on the flexible substrate, this experiment uses PET coated with a conductive coating ITO, which can be directly used as the bottom electrode to reduce the introduction of impurities. Because the substrate needs to be cleaned before preparing the biofilm and the bottom electrode (ITO) of the flexible substrate cannot be damaged, the multimeter ohmmeter is used before and after ultrasonic cleaning to test whether the bottom electrode on the surface is still conductive. At the same time, in order to further improve the performance of the resistive random access memory, SiO2 nanoparticles are introduced in the process of forming the functional layer biofilm to regulate the mesostructure, and SiO2 nanoparticles and amino-modified SiO2 nanoparticles are added to the apple gum solution respectively. The specific process is as follows: (1) Substrate pretreatment When preparing resistive random access memory on PET, it is first cleaned. Pour water into the water tank of the ultrasonic cleaning machine, select a suitable beaker, first use detergent, then deionized water, and finally ethanol, and ultrasonicate for 10 minutes respectively. Then dry the cleaned substrate and then draw the film to reduce the intervention of impurities in the process. (2) Bottom electrode test Use a multimeter to test whether the ITO surface is conductive after cleaning. Adjust the multimeter to the lowest ohm range, place the two test leads at different positions on the surface where the conductive glass is located, and repeat the test at multiple different points to observe whether it is conductive and forms a closed circuit. (3) Regulation and optimization of the functional layer SiO2 nanoparticles and amino-modified SiO2 nanoparticles were added to a 0.5wt% apple gum solution, respectively, and stirred thoroughly to form a uniform solution. The film was then prepared by the pulling method. After the pulling was completed, the substrate was dried naturally. (4) Preparation of top electrode The metal top electrode thin film such as Pt or Au on the substrate is prepared by an ion sputtering instrument, and the Pt top electrode is prepared by an ion plating instrument. First, a circular mask is placed on the surface of the substrate after plating, and a circular top electrode array is plated on the surface of the biopolymer film, which is the prepared PET (ITO) / Pectin / Pt resistive memory unit. The device has good properties such as transparency and bendability, and has a wider range of application scenarios to meet modern usage needs.
[0026] The resistive random access memory prepared by the present invention has the following advantages: (1) Environmental protection and biocompatibility: Apple gum, as a biopolymer film material, is environmentally friendly and biocompatible, which is beneficial to reducing the environmental burden of electronic products. (2) High performance: By introducing SiO2 nanoparticles for microstructure construction, the resistive random access performance and stability of the resistive random access memory are effectively improved, the turn-on voltage is reduced, and the switching ratio is increased. (3) Low cost: Apple gum raw materials are easily available and the preparation process is simple, which is beneficial to reducing production costs and promoting the commercial application of resistive random access memory.
[0027] Example 1 The present invention provides a method for preparing a resistive random access memory based on a biopolymer film, which is specifically implemented according to the following steps: Step 1: prepare a mica sheet as a substrate, and deposit a layer of Pt as a bottom electrode thereon by magnetron sputtering.
[0028] Step 2, prepare apple gum solutions with mass fractions of 0.5wt%, 1wt%, 2wt% and 3wt% respectively, use the pulling method to prepare apple gum thin film polymer on the Pt electrode, and control the pulling speed and solution concentration to obtain a uniform apple gum polymer film.
[0029] The steps of characterizing and analyzing the prepared apple gum polymer film include using ultraviolet-visible spectroscopy (UV-Vis) and atomic force microscopy (AFM), respectively. Figure 1 and Figure 2 shown. Figure 1The following is the UV-visible spectrum of apple gum polymer film with a mass concentration of 0.5wt%, and the absorbance values of apple gum polymer film at different wavelengths were tested. The absorption spectrum of apple gum has two weak peaks and one strong peak. It can be seen from the curve that the absorbance gradually decreases with the increase of wavelength. The peaks are mainly concentrated at 200-300 nm. There is a weak absorption peak at λ1=212 nm, and a π→π* transition occurs, indicating that the apple gum polymer structure contains C=C; the peak at λ2=284 nm undergoes an n→π* transition, which indicates that the apple gum polymer contains unsaturated compounds connected to heteroatoms, such as cyclic hydroxyl and carboxyl groups in the molecular configuration. Figure 2 The microscopic surface morphology of a 0.5wt% apple gum polymer film detected by atomic force microscopy, with a scanning area of 10 μm×10 μm. The film prepared on the Au-coated mica sheet can be clearly seen to be relatively flat overall, with no protrusions or holes below 2 nm. The line-shaped and cluster-shaped bright spots in the figure are the entanglement and agglomeration of some of the apple gum molecular chains.
[0030] Step 3: depositing a layer of Au as a top electrode on the apple gum polymer film again by magnetron sputtering to form a resistive random access memory with a Pt / Pectin / Au structure.
[0031] Perform IV test on the prepared resistive memory to observe and record its resistive performance, such as Figure 3 As shown, the resistive memory exhibits typical resistive behavior with a low turn-on voltage (about 0.6V) and a high switching ratio (>40).
[0032] The study was conducted using the unique microscopic force curve in atomic force microscopy, which is an innovative method to study and evaluate the micromechanics and charge transport properties of biofilms. Figure 4 The figure shows the microscopic force curve test of apple gum biopolymer film. The curve is divided into three stages: the approach stage, the needle tip gradually approaches the sample surface, the force gradually increases until it reaches the contact point; the contact stage, the needle tip contacts the sample surface, and the force reaches a relatively stable level, that is, Figure 4 Force (z=0nm): 0.906 nN; in the unloading stage, the tip is withdrawn from the sample surface and the force gradually decreases. Figure 4The snap-off phenomenon, that is, the point where the force suddenly decreases, indicates the existence of adhesion F=-1.868nN. The adhesion value of the film refers to the strength of the bond between the film and the substrate, which is crucial to the performance and reliability of the thin film device. The magnitude of the adhesion value directly affects the stability and durability of the film on the substrate and its working performance in a specific environment. In the application of bioresistive film, good adhesion can ensure close contact between the film and biological tissue or electrode, thereby improving the efficiency and accuracy of signal transmission.
[0033] Example 2 The present invention provides a method for preparing a resistive random access memory based on a biopolymer film, which is specifically implemented according to the following steps: Step 1: Prepare polyethylene terephthalate (PET) as a substrate, and coat a layer of ITO on the PET to obtain a bottom electrode.
[0034] Step 2: SiO2 nanoparticles are introduced into the apple gum solution and uniformly dispersed by stirring. The apple gum film doped with SiO2 nanoparticles is prepared on the ITO electrode by using the Czochralski method.
[0035] The prepared apple gum film was characterized and analyzed by atomic force microscopy (AFM). Figure 5 As shown, the scanning area is 10μm×10μm. The surface state of the film after doping with SiO2 nanoparticles is observed in the figure. It can be clearly seen that the local agglomeration appears as a brighter block, although other places are relatively flat. The scanning height is 40 nm.
[0036] A layer of Pt is deposited on the film by magnetron sputtering as the top electrode to form a resistive random access memory with an ITO / Pectin-SiO2 / Pt structure. During the measurement, the current limit is set to 1nA to prevent the device from being permanently broken down due to excessive current. The voltage step is 0.5 V, the step duration is 0.1 s, and the amplitude is 3 V. The IV test of the resistive random access memory is performed, such as Figure 6 As shown. Its initial resistance is about 2.17×10 5 Ω, 0V~3V devices are in high resistance state. When the forward voltage applied to the device is gradually reduced to about 0.3 V, the resistance of the device suddenly jumps. From 0.3 V to -0.5 V, the resistance decreases sharply to 5.01×10 3 Ω, it can be calculated that the switching ratio of the ITO / pectin / Au device is about 43, and it can be seen that this device exhibits a special unipolar resistance behavior.
[0037] The unique force curve in atomic force microscopy was used to study Figure 7 The figure shows the force curve test of the apple gum biopolymer film. The curve is divided into the contact stage, when the needle tip contacts the sample surface, and the force reaches a relatively stable level, that is, Figure 7 Medium Force (z=0nm): 2.741 nN; in the unloading stage, the adhesion force is F=-2.584nN.
[0038] The results are compared with the resistive memory without SiO2 nanoparticles doping to analyze the effect of doping on the resistive performance. The results show that after doping with SiO2 nanoparticles, the resistive memory exhibits different resistive behavior, and ordinary SiO2 nanoparticles doping leads to unipolar resistance behavior.
[0039] Example 3 The present invention provides a method for preparing a resistive random access memory based on a biopolymer film, which is specifically implemented according to the following steps: Polyethylene terephthalate (PET) was prepared as a substrate, and a layer of ITO was coated on the PET to obtain a bottom electrode.
[0040] Step 2: introducing aminated SiO2 nanoparticles into the apple gum solution and uniformly dispersing them by stirring. The apple gum film doped with aminated SiO2 is prepared on the ITO electrode by using the Czochralski method.
[0041] The prepared apple gum films were characterized by atomic force microscopy (AFM). Figure 8 As shown. The scanning area in the figure is 10μm×10μm, and the surface state of the film after doping with amino SiO2 nanoparticles is shown. The amino SiO2 nanoparticles are evenly dispersed on the surface of the film, and have good uniformity after film formation. There is basically no large-scale agglomeration phenomenon. The bright spots are evenly distributed in the figure. The two different SiO2 nanoparticles showed different behaviors in the test. The ordinary SiO2 nanoparticles have poor dispersion and the agglomerated grain size is about 315 nm. The grain size of the amino SiO2 nanoparticles tested is about 53 nm, which shows that the amino SiO2 nanoparticles can quickly diffuse in the solution to form a uniform solution system due to the high activity of the amino group (NH2), and will not agglomerate, so that the prepared film has relative flatness.
[0042] A layer of Pt is deposited on the film by magnetron sputtering as the top electrode to form a resistive random access memory with an ITO / Pectin-amino SiO2 / Pt structure. The resistive random access memory is tested by IV, such as Fig. 9The effect of doping on the resistive switching performance is analyzed. The initial resistance of the ITO / pectin / Au device prepared by doping amino-modified SiO2 nanoparticles with a mass fraction of 0.5wt% is 6.66×10 5 Ω, when the current increases from 0 V to 3 V, the current increases faster and faster, and the resistance changes from high resistance to low resistance, and a jump occurs at about 1.3 V, and the resistance decreases to 1.51×10 3 Ω; when the reverse voltage is applied afterwards, the device does not reach the turn-on voltage until -1.0 V, and the high resistance state can reach 6.94×10 6 Ω, the calculated switching ratio of the ITO / pectin / Au device is about 441. It can be seen that the amino-modified SiO2 nanoparticles have a very low switching ratio and a high resistance state. Although the turn-on voltage is slightly higher, it can be ignored under the limiting current of nA level.
[0043] The unique force curve in atomic force microscopy was used to study Fig.10 The figure shows the force curve test of the apple gum biopolymer film. The curve is divided into the contact stage, when the needle tip contacts the sample surface, and the force reaches a relatively stable level, that is, Fig.10 Force (z=0nm): 1.917 nN; in the unloading stage, the adhesion force is F=-3.786nN. It has a high film adhesion. Results: After doping with SiO2 nanoparticles, the resistive switching memory exhibits different resistive switching behaviors. Ordinary SiO2 doping leads to unipolar resistance behavior, while amination SiO2 nanoparticles show bipolar resistance behavior and the performance is improved.
[0044] The above description shows and describes several preferred embodiments of the invention, but as mentioned above, it should be understood that the invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and modifications made by those skilled in the art should be within the scope of protection of the claims attached to the invention without departing from the spirit and scope of the invention.
Claims
1. A method for preparing a resistive random access memory based on a biopolymer film, characterized in that: Follow the steps below to implement it: Step 1, preparing a bottom electrode; Step 2, preparing an apple gum polymer film on the bottom electrode by using a Czochralski method as a functional layer; Step 3, depositing a layer of Au as a top electrode on the functional layer by magnetron sputtering to obtain a resistive random access memory.
2. The method for preparing a resistive random access memory based on a biopolymer film according to claim 1, characterized in that: In the step 1, the bottom electrode is prepared as follows: a mica sheet is used as a substrate, and a layer of Pt or Au is deposited on the mica sheet by magnetron sputtering to obtain a bottom electrode.
3. The method for preparing a resistive random access memory based on a biopolymer film according to claim 1, characterized in that: In the step 1, the bottom electrode is prepared as follows: polyethylene terephthalate is used as a substrate, and ITO is coated thereon to obtain the bottom electrode.
4. The method for preparing a resistive random access memory based on a biopolymer film according to claim 1, characterized in that: In step 2, the preparation of the apple gum polymer film is specifically as follows: prepare an apple gum solution with a mass fraction of 0.5%, 1%, 2% or 3%, and use the pulling method to prepare the apple gum polymer film on the bottom electrode.
5. The method for preparing a resistive random access memory based on a biopolymer film according to claim 1, characterized in that: In the step 2, the apple gum solution is doped with SiO2 nanoparticles or amino SiO2 nanoparticles.